Characterization of Cu-Al-Ni melt-spun ribbons using a focussed ion beam (FIB) - Zupanič, Franc (RMZ-materials and geoenvironment, 2007)
This work investigates the possibilities for applying a focussed ion beam (FIB) for the metallographic preparation and characterization of Cu-Al-Ni melt-spun ribbons. Two alloys were selected for this reason: CuAl13Ni4 and CuAl15Ni4. The microstructure of the first alloy was fully martensitic and the microstructure of the second consisted of two phases: martensite and ?$γ_2$?. It was discovered that with FIB-etching the microstructures of both alloys can be clearly revealed on polished cross-sections of the melt-spun ribbons, as well as on their wheel-side and air-side surfaces. However, better results were obtained when the etched surface was smoother, and finer details were visible when using smaller ion currents. In addition, a study was made into the influence of platinum deposition on the quality of 3D-cross sections. It was found that Pt-deposition is necessary when the edge of the trench should be straight and sharp, and the surface of the 3D cross-section smooth. However, in this case, the microstructure of the ribbons free surface cannot be seen.
Keywords: zlitine; baker; aluminij; Aluminij Mostar; aluminum; nikelj; trakovi; metalografija; mikrostruktura; ionski curek; litje